An exploratory analysis of divergent patterns in reading progression during a tablet-based literacy program - Bardack, Sarah; Lopez, Celeste; Levesque, Karen; Chigeda, Antonie; Winiko, Symon (Frontiers in Education, 2023)
We conducted exploratory research on divergent patterns in reading progression among early grade learners in a low-resourced community to identify key determinants of high versus low reading progress. The sample comprised 30 learners who were purposively selected from participants in a 13-month tablet-based literacy program at a peri-urban Malawi primary school to represent high and low progressing readers. We employed stepwise logistic regression to test the independent contributions of (1) a composite measure of home literacy and language environment, and (2) a direct assessment of working memory skills, to a binary measure of reading progress status, controlling for children’s age. Our results showed that children’s working memory skills uniquely predicted high versus low progress in reading over and above other known predictors of early literacy development. These findings point to the importance of working memory skills as a key determinant of reading progress in the context of a tablet-based literacy program in a developing country. As education technology programs proliferate in low-income countries, results from our study offer an evidence-based strategy for identifying and supporting learners who are at risk for non-progress in reading during a tablet-based literacy intervention